A heat recovery unit with phase change material for combi‐boilers. Issue 5 (8th August 2019) - Balci, Ozan M; Ezan, Mehmet A; Turhan, Kutbettin Z
Abstract: A novel heat exchanger (HEX) with phase change material (PCM) is proposed to recover the waste heat from the flue gas of a combi‐boiler. The thermal energy that is recovered from the flue gas is stored within the PCM‐HEX when the combi‐boiler works in the central heating mode. The stored thermal energy is then released to pre‐heat the domestic water so that the combi‐boiler provides the domestic water at a required temperature more rapidly even in eco‐mode. A mathematical model is developed, and the discharging process of the PCM‐HEX is considered. The transient analyses are conducted to reveal the influences of the mass of PCM, the phase change temperature of the PCM, and the flow rate of the domestic water. It is found that the PCM‐HEX integrated combi‐boiler increases the domestic water temperature in the early period of the hot water demand. Results show that the water temperature increases as much as Δ T = 9.3°C and 19.2°C for the flow rates of 10 L/min and 3 L/min, respectively. Increasing the water temperature with the PCM‐HEX not only helps to reduce the waiting time of the end‐user but also improves the efficiency of the combi‐boiler and reduces the energy consumption.